Replacing mechanical protection with colorful faces–twice: parallel evolution of the non-operculate marine worm-snail genera Thylacodes (Guettard, 1770) and Cayo n. gen. (Gastropoda: Vermetidae) - Rüdiger Bieler; Timothy M. Collins; Rosemary Golding; Camila Granados-Cifuentes; John M. Healy; Timothy A. Rawlings; Petra Sierwald (PeerJ, 2023)
Vermetid worm-snails are sessile and irregularly coiled marine mollusks common in warmer nearshore and coral reef environments that are subject to high predation pressures by fish. Often cryptic, some have evolved sturdy shells or long columellar muscles allowing quick withdrawal into better protected parts of the shell tube, and most have variously developed opercula that protect and seal the shell aperture trapdoor-like. Members of Thylacodes (previously: Serpulorbis) lack such opercular protection. Its species often show polychromatic head-foot coloration, and some have aposematic coloration likely directed at fish predators. A new polychromatic species, Thylacodes bermudensis n. sp., is described from Bermuda and compared morphologically and by DNA barcode markers to the likewise polychromatic western Atlantic species T. decussatus (Gmelin, 1791). Operculum loss, previously assumed to be an autapomorphy of Thylacodes, is shown to have occurred convergently in a second clade of the family, for which a new genus Cayo n. gen. and four new western Atlantic species are introduced: C. margarita n. sp. (type species; with type locality in the Florida Keys), C. galbinus n. sp., C. refulgens n. sp., and C. brunneimaculatus n. sp. (the last three with type locality in the Belizean reef) (all new taxa authored by Bieler, Collins, Golding & Rawlings). Cayo n. gen. differs from Thylacodes in morphology (e.g., a protoconch that is wider than tall), behavior (including deep shell entrenchment into the substratum), reproductive biology (fewer egg capsules and eggs per female; an obliquely attached egg capsule stalk), and in some species, a luminous, “neon-like”, head-foot coloration. Comparative investigation of the eusperm and parasperm ultrastructure also revealed differences, with a laterally flattened eusperm acrosome observed in two species of Cayo n. gen. and a spiral keel on the eusperm nucleus in one, the latter feature currently unique within the family. A molecular phylogenetic analysis based on mitochondrial and nuclear rRNA gene sequences (12SrRNA, trnV, 16SrRNA, 28SrRNA) strongly supports the independent evolution of the two non-operculate lineages of vermetids. Thylacodes forms a sister grouping to a clade comprising Petaloconchus, Eualetes, and Cupolaconcha, whereas Cayo n. gen is strongly allied with the small-operculate species Vermetus triquetrus and V. bieleri. COI barcode markers provide support for the species-level status of the new taxa. Aspects of predator avoidance/deterrence are discussed for these non-operculate vermetids, which appear to involve warning coloration, aggressive behavior when approached by fish, and deployment of mucous feeding nets that have been shown, for one vermetid in a prior study, to contain bioactive metabolites avoided by fish. As such, non-operculate vermetids show characteristics similar to nudibranch slugs for which the evolution of warning coloration and chemical defenses has been explored previously.